Two new species of Coelostoma Brullé, 1835 from China and additional faunistic records of the genus from the Oriental Region (Coleoptera: Hydrophilidae: Sphaeridiinae: Coelostomatini) - Jia, Fenglong; Lin, Renchao; Chan, Eric; Skale, Andre; Fikáček, Martin (Zootaxa, 2017)
Two new species of Coelostoma Brullé, 1835 are described from China: C. (Lachnocoelostoma) jaechi sp. nov. (Hong Kong) and C. (Lachnocoelostoma) tangliangi sp. nov. (Hainan). Coelostoma (s. str.) subditum Orchymont, 1936 is reported for the first time from continental Asia (China: Hong Kong, Yunnan). The first country or province records are provided for an additional 10 species: C. (s. str.) vividum Orchymont, 1936 from Cambodia and Pakistan, C. (s. str.) vitalisi Orchymont, 1923 from Cambodia and Thailand; C. (Holocoelostoma) stultum (Walker, 1858) from Myanmar and China: Hainan, Chongqing; C. (Lachnocoelostoma) coomani Orchymont, 1932 from China: Guizhou, Sichuan; C. (L.) hongkongense Jia, Aston & Fikáček, 2014 from Thailand and China: Yunnan; C. (L.) horni (Régimbart, 1902) from Thailand; C. (L.) huangi Jia, Aston & Fikáček, 2014 from Thailand; C. (L.) phallicum Orchymont, 1940 from China: Yunnan; C. (L.) vagum Orchymont, 1940 from China: Fujian; and C. (L.) wui Orchymont, 1940 from China: Fujian, Henan. Coelostoma coomani diversum Orchymont, 1932 is elevated to species rank (as C. diversum stat. nov.) based on the study of its type specimens and comparison with species treated here. An updated key to the species of Chinese Coelostoma is provided.